Second-generation proteasome inhibitor carfilzomib enhances doxorubicin-induced cytotoxicity and apoptosis in breast cancer cells - Shi, Yonghua (Oncotarget, 2016)
Proteasome inhibition is an attractive approach for anticancer therapy. Doxorubicin (DOX) is widely used for treatment in a number of cancers including breast cancer; however, the development of DOX resistance largely limits its clinical application. One of the possible mechanisms of DOX-resistance is that DOX might induce the activation of NF-κB. In this case, proteasome inhibitors could inhibit the activation of NF-κB by blocking inhibitory factor κB (IκB) degradation. Carfilzomib, a second-generation proteasome inhibitor, overcomes bortezomib resistance and lessens its side-effects. Currently, the effect of carfilzomib on breast cancer cell proliferation remains unclear. In this study, we exploited the role of carfilzomib in seven breast cancer cell lines, MCF7, T-47D, MDA-MB-361, HCC1954, MDA-MB-468, MDA-MB-231, and BT-549, representing all major molecular subtypes of breast cancer. We found that carfilzomib alone had cytotoxic effects on the breast cancer cells and it increased DOX-induced cytotoxic effects and apoptosis in combination by enhancing DOX-induced JNK phosphorylation and inhibiting DOX-induced IκBα degradation. The results suggest that carfilzomib has potent antitumor effects on breast cancer in vitro and can sensitize breast cancer cells to DOX treatment. DOX in combination with carfilzomib may be an effective and feasible therapeutic option in the clinical trials for treating breast cancer.